Comparison of Biological Attributes of Culex quinquefasciatus (Diptera: Culicidae) Populations from India. (13th June 2013) - Gokhale, Mangesh D.; Paingankar, Mandar S.; Dhaigude, Sachin D.
Abstract : Understanding the population dynamics of mosquito populations through life table analysis and insecticide susceptibility is important to assess the likely impact of vector control strategies as well as to aid the design of novel interventions. Variation in the life tables and other biological data was compared for two populations of Culex quinquefasciatus Say 1823 from geographically isolated regions, Gorakhpur and Pune from India. Under a standardized rearing regime and constant laboratory conditions, mosquitoes were reared and biological attributes of these populations were compared. Development and survival of immature and adult stages of Culex quinquefasciatus were found significantly different in Gorakhpur and Pune populations. Principal component analysis of morphological data revealed that the two populations form significantly different clusters which can be differentiated from each other based on siphon, saddle, anal gills, and pecten teeth related variables. Insecticide susceptibility results suggest that the larvae from both areas were more susceptible to deltamethrin as compared to DDT and malathion. The current study provides baseline information on survivorship, morphological variation and insecticide susceptibility of Culex quinquefasciatus . The results obtained in this study suggest that different geographical areas with contrasting habitats have significant influence on survival and reproductive strategies of Culex quinquefasciatus .